Perbedaan Aktivitas dan Hasil Belajar Siswa Menggunakan Problem Based Learning dan Discovery Learning pada Bahan Ajar Laju Reaksi Terintegrasi Nilai Spiritual - Salwa Syafirah; Ayi Darmana (ARKA INSTITUTE, 2022)
This study aims to determine the differences in learning activities, learning outcomes and student spirituality between learning using the Problem Based Learning (PBL) model and the Discovery Leaning (DL) model on reaction rate material Integrated with Spiritual Values. The population in this study were all XI MIA classes consisting of two classes. All populations were taken as samples (total sample). Class XI MIA 1 is used as an experimental class 1 using PBL learning while class XI MIA 2 as an experimental class 2 with the DL model. The instruments used in this study are two, namely test and non-test instruments. Test instruments to measure learning outcomes in the form of multiple choice as many as 20 questions that are valid and reliable. Non-test instruments in the form of student learning activity observation sheets and questionnaires used to measure student spirituality. The results showed, for experimental class 1: activity 85.55 learning outcomes 72.22 and spiritual attitudes 85.58. While the experimental class 2: activity 75.50 learning outcomes 72.22 and spiritual attitude 81.27. From statistical testing obtained sig (0.0001) < α (0.05) for activity, while for learning outcomes sig (0.002) < α (0.05) H0 is rejected and Ha is accepted, while for spiritual attitudes obtained sig value (0.079) > α (0.05) H0 is accepted and Ha is rejected. Thus, it can be concluded that there is a significant difference in activity and learning outcomes and no difference for the spiritual attitude of students using PBL and DL on reaction rate material Integrated spiritual values.